Referral and Prosecution Authority before the International Criminal Court According to the 1998 Rome Statute - Al Al-Jasmi, Nouf; Al Ghawari, Zayed (Journal of Legal Sciences, 2022)
The ICC is a reclining judicial body that punishes ordinary persons for crimes committed and falls within its jurisdiction in accordance with article (5) of the Court's Statute: crimes of extermination, war, aggression, and crimes against humanity. This gives the international community the right as affected by these acts to initiate criminal proceedings to punish the perpetrator. However, this right has not been left so and without regulation, but has been enshrined in the Rome Statute - whether with regard to those who are qualified to exercise this right, or with the restrictions to which it responds, requiring the ICC to exercise its powers to take some previous actions in contact with the Court in connection with the case, the most important of which is to refer the case either through a State party, or not by a party, or through the Security Council - in relation to any situation that threatens peace and international security to the Prosecutor of the Court, and the prosecutor The general investigation after he was authorized by the Pretrial Affairs Department.